(untitled) (Al-Aasar, 2025)
The Seerah of Prophet Muhammad PBUH has long been examined by Western scholars, commonly described as Orientalists. Their studies often reflect methodological assumptions shaped by Western intellectual traditions, colonial contexts, and limited engagement with classical Islamic sources. As a result, Orientalist writings have raised objections and interpretations concerning the Prophet’s PBUH prophethood, personal life, marriages, military campaigns, and socio-political role. This study offers a critical and analytical review of major Orientalist perspectives on the Seerah, assessing their arguments in light of historical evidence and authentic Islamic sources. It examines the intellectual foundations of these objections and identifies recurring patterns of misinterpretation and contextual distortion. The article also presents responses of Muslim scholars who have addressed these claims through rigorous scholarship grounded in Qur’an, Hadith, and early Islamic historiography. By comparing Orientalist narratives with Islamic counter-arguments, this research highlights the limitations of biased readings and emphasizes the need for contextual and source-based analysis. The study contributes to a clearer understanding of how Orientalist scholarship has shaped modern perceptions of the Prophet Muhammad, PBUH. It underscores the importance of critical engagement in the study of Islamic history.